A REVIEW OF GRADUATE THESES ON DISASTER MANAGEMENT IN HIGHER EDUCATION IN TÜRKİYE (Third Sector Social Economic Review, 2023)
The aim of this study is to determine the research tendencies of universities in the field of disaster management in higher education. The study examined 86 master's and doctoral theses on ""Disaster Management in Higher Education"" written between 2003 and 2022 to identify research trends in universities. The study used descriptive and content analysis methods to evaluate the current status of the topic, method, analysis techniques, and trends. To find the relevant studies, keywords such as ""disaster"", ""disaster management"", ""higher education"", ""university"", ""student"", ""staff"", and ""policy"" were used in the Higher Education Council (YÖK) National Thesis Center. The results showed that the number of theses focused on ""disaster management in higher education"" has increased significantly in the last four years. The majority of the studies were conducted in Çanakkale Onsekiz Mart University. Another finding is that in disaster management theses in higher education, female researchers represent 49%, while male researchers constitute 51%, and empirical studies have been identified as the most commonly used research method. The disaster management system was primarily addressed in the ""preparedness"" dimension, and universities conducted research in the public domain to contribute to society in disaster management. However, the study suggested that universities should focus on areas related to the university's framework conditions for disaster management. In conclusion, the study provides universities with recommendations and implications for future research to improve their understanding and approaches towards disaster management in higher education.
Keywords: disaster management; research trends; graduate theses; content analysis; higher education studies